가상현실 기반 교통사고 위험예측 검사 개발 연구 - 오주석; Oh Ju-seok; 류준범; Ryu Jun-beom (교통안전연구, 2023)
본 연구에서는 운전자들의 교통사고 위험성을 평가하여 예방활동에 기여할 수 있는 가상현실 기반의 위험 예측능력 검사를 개발하고자 하였다. 운전자들을 대상으로 설문조사를 실시하여 교통사고 또는 교통사고가 날 뻔했던 경험에 대한 사항들을 조사하여 이를 토대로 교통사고 위험상황 기초시나리오 20건을 도출하였다. 각 시나리오에 대한 사고 빈도와 심각도, 교육을 통한 개선 효과성에 대해 전문가들로 하여금 평정하도록 하였으며, 이에 근거하여 총 12건의 최종시나리오를 선정 한 후 교통사고 위험예측 검사 프로그램으로 구현하였다. 위험예측 검사 프로그램의 사용성 평가 결과, 영상의 품질과 실제 운전상황과의 유사성, 반응장치의 작동 적절성 및 교육 효과성 등에서 긍정적인 평가를 받았으며 멀미 등의 신체적 불편감 역시 적은 것으로 확인되었다. 추후 프로그램 개선을 통해 운전자 반응시간의 조작적 정의를 더욱 구체화 하고 평가 결과에 대한 적절한 피드백이 제공될 수 있도록 표준화 연구 및 평가체계 개발의 필요성을 제기하였다. This study aimed to develop a virtual reality-based hazard predictive ability test to contribute to preventive activities by assessing drivers’ risk of traffic accidents. A survey of drivers investigated the experiences of traffic accidents or near accidents, from which we derived 20 basic traffic accident risk scenarios. Experts evaluated the frequency and severity of accidents, and the effectiveness of traffic safety education for each scenario. Twelve scenarios were selected and developed for the hazard prediction test using virtual reality. As a result of the usability evaluation of the hazard prediction test program, the visual quality, situation reality, quality of the reaction device, and the effectiveness of training were evaluated positively. Physical discomfort such as motion sickness was also confirmed to be low. We also discussed the need to further refine the operational definition of driver reaction times through program improvements, the need for standardization research, and the development of an evaluation system to provide appropriate feedback on test results.